الصلح بين الزوجين في ضوء التعديلات التشريعيَّة لقانون الأحوال الشخصية الإماراتي لسنة2020 - دراسة لأحكام القانون والشريعة: Reconciliation between spouses in light of the legislative amendments to the UAE Personal Status Law in 2020 - A study of the provisions of law and Sharia - Alkindi, Ali Saif Mohammed; Muhammad Najib Bin Abdullah; Muhamad Firdaus Bin Abd Rahman (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث هدفت الدراسة إلى التعرف على التعرف الصلح بين الزوجين في ضوء التعديلات التشريعيَّة لقانون الأحوال الشخصية الإماراتي سنة 2020 من خلال دراسة لأحكام القانون الاماراتي واحكام الشريعة الإسلامية وتناولت الدراسة مدى توافق الشريعة الإسلامية والقوانين الوضعية في تحقيق الصلح على أكمل وجه، وذلك باتخاذ كل السبل والآليات الكفيلة بذلك. ولقد برزت أهمية الدراسة من خلال إظهار المصالحة والوساطة في تحقيق الأمن الأسري في ضوء الشريعة الإسلامية والقانون الوضعي. إن الوساطة والصلح من أكثر الطرق فعالية لتحقيق الإصلاح والتوجيه الأسري وخفض نسب دعاوى الطلاق، وبيان قياس مدى أثر التعديلات التشريعية لقانون الأحوال الشخصية 2020 وإيجاد نصـوص قانونيـة خاصـة تتبنـى نظريـة عامـة للصـلح بين الزوجين في قانون الأحوال الشخصية الإماراتي، اتبعت الدراسة المنهج الوصفي التحليلي لوصف وتحليل الصلح في الشريعة الإسلامية والقانون الوضعي الإماراتي. كما تناولت الدراسة المنهج الاستقرائي لاستقراء نصوص القرآن الكريم، والسنة النبوية المطهرة، واحكام الشريعة والقوانين الوضعية ومقارنتها بنصوص القانون الوضعي ونصوص القرآن الكريم والسنة النبوية. وتوصلت الدراسة إلى العديد من النتائج، من أهمها أن المصالحة والصلح لها دور كبير في تحقيق الأمن الأسري وإنشاء مراكز الإصلاح والتوجيه الأسري تسهم في خفض نسب دعاوى الطلاق. ABSTRACT The study aimed to identify reconciliation between spouses in light of the legislative amendments to the UAE Personal Status Law in 2020 through a study of the provisions of Emirati law and the provisions of Islamic Sharia. The study addressed the extent to which Islamic Sharia and statutory laws are compatible in achieving reconciliation to the fullest extent, by taking all means and mechanisms to do so. The importance of the study emerged by demonstrating reconciliation and mediation in achieving family security in light of Islamic law and positive law. Mediation and reconciliation are among the most effective ways to achieve family reform and guidance, reduce the rates of divorce lawsuits, demonstrate the extent of the impact of the legislative amendments to the Personal Status Law 2020, and create special legal texts that adopt a general theory of reconciliation between spouses in the UAE Personal Status Law. The study followed the descriptive analytical approach to describe and analyze reconciliation in Islamic law and UAE positive law. The study also dealt with the inductive approach to extrapolating the texts of the Holy Qur’an, the purified Sunnah of the Prophet, the provisions of Sharia and positive laws, and comparing them with the texts of positive law, the texts of the Holy Qur’an and the Sunnah of the Prophet The study reached many results, the most important of which is that reconciliation and reconciliation have a major role in achieving family security, and the establishment of reform and family guidance centers contributes to reducing the rates of divorce lawsuits.